Public Information Disclosure and Crisis Communication in the Time of the COVID-19 Outbreak - Safaria, Anne Friday; Malik, Dedy Djamaluddin; Rachmiatie, Atie (Mediator: Jurnal Komunikasi, 2025)
This article aims to determine how the government implemented public information disclosure and crisis communication management during the COVID-19 pandemic. Theoretically, crisis communication is divided into three phases: pre-crisis, crisis phase, and post-crisis. This article uses a qualitative approach by framing  (qualitative content analysis) issues related to crisis communication. Data collection comes from government media outlets as primary data and non-government media, books, journal articles, and other documents as secondary data. This study found that the content of the information conveyed is divided into three phases of crisis communication. Still, the government has been unable to handle crisis communication during the COVID-19 pandemic optimally. This is due to a lack of preparation in collecting pandemic data, a lack of coordination between institutions and elites, and the failure to disseminate public information that has not been widespread across all regions/provinces. This research is expected to contribute to the theory and practice of Public Administration and Communication, particularly in formulating and implementing public policies for crisis communication management in dealing with future crises.